Field Identification of Citrus Canker Symptoms and Decontamination Procedures - Mongi Zekri; Megan Dewdney; Jamie Burrow; Pamela Roberts (EDIS, 2019)
This 5-page fact sheet is a minor revision written by Mongi Zekri, Megan Dewdney, Jamie Burrow, and Pamela Roberts, and published by the Plant Pathology Department, March 2019.